Frequency of fungal pathogens in autopsy studies of people who died with HIV in Africa: a scoping review - Bongomin, Felix; Kibone, Winnie; Atulinda, Linda; Morgan, Bethan; Ocansey, Bright; Storer, Isabelle S.R.; Rhijn, Norman van; Muzoora, Conrad; Denning, David W.; Hamer, Davidson H. (Clinical Microbiology and Infection, 2023)
Background: Fungal infections are common in HIV-infected individuals and significantly contribute to mortality. However, a substantial number of cases are undiagnosed before death. Objective: To determine the frequency of fungal pathogens in autopsy studies of people who died with HIV in Africa. Methods: We conducted a scoping review of autopsy studies conducted in Africa. Data sources: PubMed, Scopus, Web of Science, Embase, Google Scholar, and African Journal Online. Study eligibility criteria: The review encompasses studies published from inception to September 2023, and no language restrictions were imposed during the search process. We included studies that reported histopathological or microbiological evidence for the diagnosis of fungal infections and other pathogens. Data synthesis: Data were summarized using descriptive statistics and no meta-analysis was performed. Results: We examined 30 articles reporting studies conducted between 1991 and 2019, encompassing a total of 13 066 HIV-infected decedents across ten African countries. In five studies, the autopsy type was not specified. Among those studies with specified autopsy types, 20 involved complete diagnostic au topsies, whereas 5 were categorized as partial or minimally invasive autopsies. There were 2333 pathogens identified, with 946 (40.5%) being mycobacteria, 856 (36.7%) fungal, 231 (3.8%) viral, 208 (8.9%) parasitic, and 92 (3.9%) bacterial. Of the 856 fungal pathogens identified, 654 (28.0%) were Cryptococcus species, 167 (7.2%) Pneumocystis jirovecii , 16 (0.69%) Histoplasma species, 15 (0.64%) Aspergillus species, and 4 (0.17%) Candida species. Other major non-fungal pathogens identified were cytomegalovirus 172 (7.37%) and Toxoplasma gondii 173 (7.42%). Conclusions: Invasive fungal infections occur in over one-third of people who succumb to HIV in Africa. In addition to cryptococcosis and Pneumocystis jirovecii pneumonia, integrating other priority fungal pathogen detection and management strategies into the broader framework of HIV care in Africa is recommended. This involves increasing awareness regarding the impact of fungal infections in advanced HIV disease and strengthening diagnostic and treatment capacity.
Keywords: Advanced HIV disease; Africa; AIDS; Autopsy; Fungal pathogens; Opportunistic infections